THE ROLE OF PROFESSIONAL ETHICS OF PAI TEACHERS IN THE IMPLEMENTATION OF LEARNING IN SCHOOLS - Nur Alfil Lail; Balqis Raisa Labibah; Abd Mukhid; Adila Al-Mafaiz H. Yady; Mohammad Fauzhul Adhim (SOSIOEDUKASI, 2026)
This research was motivated by the importance of professional ethics of Islamic Religious Education (PAI) teachers in supporting the success of the learning process and the formation of students’ character in madrasah. The task of an Islamic Religious Education (PAI) teacher is not limited to transmitting lesson material alone, but they are also required to provide real examples in applying Islamic values within the school environment. This study aims to analyze three main aspects: first, to find the role of teacher work ethics in the learning process at MIN 1 Sumenep; second, to explain how work ethics are applied in each teaching technique; and third, to identify obstacles and solutions faced by PAI teachers in shaping student character. The research method uses a qualitative approach with a case study type. Data collection was carried out through three techniques, namely interviews, field observations, and documentation with purposive sampling techniques applied to PAI teachers at MIN 1 Sumenep. Data analysis utilizes the Miles and Huberman model with three main stages: data reduction, data presentation, and drawing conclusions. The research results reveal that the work ethic of PAI teachers plays a vital role in efforts to create a conducive learning atmosphere, foster student discipline, and build the religious character of students in daily life. Nevertheless, in its implementation in the field, several obstacles are faced by teachers, including the impact of technological advancement, the social conditions around the school, as well as the presence of students who are still less disciplined. To address these problems, several strategies are applied by teachers, including strengthening religious-themed activities, implementing varied learning methods, and building intensive communication with students' guardians. Based on this description, it can be concluded that the professionalism of PAI teachers provides a significant contribution to the smoothness of the learning process as well as the character formation of students in the madrasah environment.